Approach and mechanism of toughness enhancement for a high carbon Q-P-T steel. Issue 1 (3rd April 2019) - Qin, Shengwei; Liu, Yu; Zhang, Jiazhi; Wang, Ying; Rong, Yonghua; Zuo, Xunwei; Chen, Nailu
ABSTRACT: Based on the previous study of Cr-containing Fe-0.63C-1.52Mn-1.49Si-0.62Cr-0.036Nb high carbon steel, although normalization process as a pretreatment of quenching–partitioning–tempering (Q-P-T) was performed in this high carbon steel to raise the ductility, its impact toughness only is 7.4 J/cm 2 . Microstructural characterization reveals that strain-induced twin-type martensite transformed from considerable chunky retained austenite destroys toughness. Therefore, a novel Cr-free Fe-0.67C-1.52Mn-1.49Si-0.038Nb (wt.%) high carbon steel was designed and normalization process as pretreatment of Q-P-T process was still employed so that the volume fraction of retained austenite evidently decreases from 21% to 10%. This high carbon steel not only keeps high tensile strength (1660 MPa) and elongation (29.0%), but also exhibits high impact toughness of 33.2 J/cm 2 . The high impact toughness is attributed to the elimination of chunky retained austenite accompanying dispersive and fine retained austenite with high mechanical stability, which effectively reduces the formation of brittle strain-induced twin-type martensite during deformation.